First record of Capillaria boehmi (syn. Eucoleus boehmi) (Supperer, 1953) in a domestic dog from southern Brazil - Ferraz, Alexsander (2025)
Capillaria boehmi (syn. Eucoleus boehmi) (Supperer, 1953) is a nematode of the Trichuridae family that infects the upper respiratory tract of definitive hosts, primarily wild and domestic canids. Transmission occurs through the ingestion of embryonated eggs, eliminated in the feces or nasal secretions of infected animals, or through the ingestion of earthworms, which are considered intermediate/paratenic hosts of the parasite. Therefore, the aim of this study was to report the first case of Capillaria boehmi in a domestic dog in southern Brazil. The fecal sample analyzed was collected from an adult male mixed-breed dog. The animal had recurrent episodes of sneezing and had been previously diagnosed and treated, unsuccessfully, as an allergic condition. In the coproparasitological examination, using the flotation technique in a hypersaturated solution, eggs of Capillaria boehmi were observed. The instituted treatment was milbemycin oxime (2 mg/kg). This report highlights the importance of including Capillaria boehmi in the differential diagnosis of dogs with chronic respiratory signs, especially when other common causes, such as bacterial, viral, or allergic infections, have been ruled out.